10-year prevalence of diagnostic and screening colonoscopy use in Germany: a claims data analysis. Issue 6 (4th January 2022) - Hornschuch, Michel; Schwarz, Sarina; Haug, Ulrike
Abstract : Introduction: Studies providing detailed information on colonoscopy use are important for the interpretation of patterns and trends in colorectal cancer incidence and mortality, but there is a lack of such studies from Germany. To fill this gap, we aimed to describe the 10-year prevalence of colonoscopy use based on German health claims data. Methods: Using the German Pharmacoepidemiological Research Database (short GePaRD; claims data from 20% of the German population), we determined the 10-year prevalence of colonoscopy use for the year 2017. We determined this prevalence for any colonoscopy, screening (reimbursable from age 55) and diagnostic colonoscopy, stratified by sex, age, educational level and regional factors (e.g. federal state, physicians density in the district of residence). Results: In men, the 10-year prevalence of colonoscopy use was as follows (not all age groups reported): 30–34 years: 8%, 40–44 years: 12%, 50–54 years: 21%, 55–59 years: 33% (screening: 10%), 60–64 years: 44% (screening: 23%), 70–74 years: 53% (screening: 23%), 80–84 years: 52% (screening: 15%). In women, the prevalences were similar, with differences mostly less than or equal to 3 percentage points. Also, in analyses stratified by educational level or regional factors, prevalences were mostly similar or varied by less than or equal to 4 percentage points. Conclusion: In 2017, about 45–50% of men and women in Germany aged 60–84 years had any colonoscopy in the previous 10 years, and about 11–26% had a screening colonoscopy. Our findings suggest no relevant social or regional disparities in the utilization of colonoscopy in Germany.